2020
DOI: 10.3390/ijms21103544
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipid Metabolism in COVID-19 Virus Infection and as a Drug Target

Abstract: The current Coronavirus disease 2019 or COVID-19 pandemic has infected over two million people and resulted in the death of over one hundred thousand people at the time of writing this review. The disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Even though multiple vaccines and treatments are under development so far, the disease is only slowing down under extreme social distancing measures that are difficult to maintain. SARS-COV-2 is an enveloped virus that is surrounded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
231
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(256 citation statements)
references
References 90 publications
(101 reference statements)
5
231
0
7
Order By: Relevance
“…As a coronavirus requiring lipids for reproduction, COVID-19 can be expected to disrupt the lipidome. 15 Evidence of dysregulated lipidomes have recently been observed in patients with COVID-19 via analyses of blood plasma and also by lipidomic analysis of nasopharyngeal swabs, 16,17 and dysregulation of the skin would be consistent with the ability of canines to differentiate COVID-19 positive and negative by smell. 18 Lipidomics therefore offers a promising route to better understanding of -and potentially diagnosis and prognosis for -COVID-19.…”
Section: Introductionmentioning
confidence: 78%
“…As a coronavirus requiring lipids for reproduction, COVID-19 can be expected to disrupt the lipidome. 15 Evidence of dysregulated lipidomes have recently been observed in patients with COVID-19 via analyses of blood plasma and also by lipidomic analysis of nasopharyngeal swabs, 16,17 and dysregulation of the skin would be consistent with the ability of canines to differentiate COVID-19 positive and negative by smell. 18 Lipidomics therefore offers a promising route to better understanding of -and potentially diagnosis and prognosis for -COVID-19.…”
Section: Introductionmentioning
confidence: 78%
“…Also, SARS-CoV-2 regulates the lipidic metabolism to generate viral membrane and pack its genome and in the exocytosis of the virions 40,41 . For this reason, a growing recent interest in the lipids changes research has been noted in SARS-CoV-2 infected patients, since people with metabolic diseases such as DM, HT, and obesity, possibly leading to a higher risk of complications and mortality from COVID-19 42,43 . Our study found high frequencies of comorbidities alone or in combination, such as HT, DM, and obesity in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a benchmark, the encapsidated RNAs within the positive controls were extracted using QIAGEN QIAamp Viral RNA mini kit; the procedure followed CDC recommendations. One difference to note between SARS-CoV-2 and our control probes is that SARS-CoV-2 is an enveloped virus, 49 but our control probes based of Qβ and CCMV are non-enveloped viruses.…”
Section: Validation Of the Vlp-based Sars-cov-2 Positive Controlsmentioning
confidence: 98%